"You're putting words in my mouth!": Interaction as mutual ventriloquation. Issue 1 (2nd January 2023) - Cooren, François; Brummans, Boris H. J. M.; Higham, Lise
ABSTRACT: The accusation that someone is putting words in someone else's mouth can be heard in everyday conversations, but what does this phenomenon reveal about the ways human beings communicate? This paper aims to show that it is useful to view putting words in someone's mouth as a form of ventriloquation. By theorising this phenomenon, this paper explicates how people discover a version of what they said in their interlocutors' mouths, and in turn react to these ventriloquations. Since this phenomenon is especially visible in conflict situations, this paper demonstrates the value of using a ventriloquial lens to study human interactions through a detailed analysis of a public dispute and a conflict mediation session. Thus, this paper shows how this lens can be used to gain insight into the communicative constitution of conflict as well as its resolution. More broadly, it proposes to conceive of interaction as a process of mutual ventriloquation and highlights the methodological, ethical, and political implications of this analytical move.